The Role of Patient Satisfaction in Mediating the Influence of Brand Image and Price on Inpatient Decision-Making (Non-JKN Patients): A Case Study - I Nyoman Armita; Ida Ayu Oka Martini (Indonesian Journal of Global Health Research, 2025)
Marketing is one of the core activities that must be undertaken by both goods and service companies, including hospitals. Various hospitals implement different strategies to enhance public trust in their services. This study aims to analyze and explain the mediating role of patient satisfaction in the relationship between brand image and price on inpatient decision-making among non-JKN patients. This study was a quantitative research employing a case study approach, conducted at Siloam Hospital Denpasar. The sample was choshen by purposive sampling. The total number of respondents was 100 non-JKN (non-national health insurance) inpatients. The research instrument used was a questionnaire measuring satisfaction related to brand image and decision-making among non-JKN patients. The analysis technique employed was Structural Equation Modeling (SEM) using the Partial Least Squares (PLS) approach. The R-square value for the influence of brand image and price on patient decision-making was 0.772, indicating a substantial effect (77.2%). This means that brand image and price influence patient decisions by 77.2%, while the remaining 22.8% is influenced by other variables. The R-square value for the influence of brand image and price on patient satisfaction was 0.636, also indicating a strong effect (63.6%), with the remaining 36.4% influenced by other factors. The findings indicate that brand image has a positive and significant influence on the decision-making of non-JKN inpatients at Siloam Hospital Denpasar.